KONTRIBUSI SIKAP ORANG TUA TERHADAP KEMANDIRIAN ANAK - Triyono (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2020)
This research is motivated by the existence of parents who educate their children in excessive ways and will lead their children to negative influences in the future. The attitude of the parents is thought to be related to the child's independence. This study aims to examine the contribution between parents' attitudes and children's independence at SM Aur 01 Sungai Aur, West Pasaman Regency. This research uses quantitative correlational type method. The research population was VIII grade students of SMPN 01 Sungai Aur, West Pasaman Regency with a total of 195 respondents, a sample of 130 respondents, selected by proportional stratified random sampling technique. The instrument used was a questionnaire. Data were analyzed by simple linear regression using the SPSS program. The results showed that there was a contribution between parents' attitudes and children's independence at SM Aur 01 Sungai Aur, West Pasaman Regency which was equal to (R 4.1% and significant rtable 0.021). This means that the level of independence of a child is not only influenced by the attitude of parents, but there are still many other factors that influence.